P53 Epidemiological evidence to support a tax on Sugar Sweetened Drinks as a measure to address childhood obesity. (13th September 2016) - Harrington, JM; Perry, C; Ryan, K; Keane, E; Perry, IJ
Abstract : Background: The obesity epidemic represents a public health crisis with the potential to reverse recent favourable trends in life expectancy and undermine the financial viability of health systems. Though multifactorial in origin, links between the consumption of sugar-sweetened drinks (SSD) and excessive weight gain in children have been observed. Aim: To investigate the association between SSD consumption and overweight and obesity in 8–11 year old children. Methods: Cross sectional data from 1075 8–11 year old school children. Consumption of SSD was assessed from 3-day food diaries. Height (m) and weight (kg) were measured using standard methods. BMI was used to define obesity (IOTF definitions). Plausible energy reporters (PER) were classified using Scholfield equation. Results are reported for PER only Results: Eighteen percent of children with PER were overweight (16%) or obese (2%) compared with 25% of the total sample. Of those with PER, 82% were SSD consumers. Consumers had increased odds of being overweight or obese compared to normal weight children. Mean calories from SSDs increased incrementally between weight categories: SSD contributed 86 kcal, 117 kcal and 274 kcal for normal weight, overweight and obese children respectively, equating to 4.7%; 6.1% and 10.7% of total calories respectively. Mean intake volumes were significantly higher in children who were overweight or obese compared to normal weight children. Average consumption volume was 487 ml/d; 368 ml/d and 315 ml/d for obese, overweight and normal weight children respectively. Adjusting for gender and parental education, an increase of one can per day (330 ml) is associated with a 0.51 kg/m 2 (95% CI [0.21–0, 81]) increase in BMI. Conclusion: While no single measure will reverse current trends in obesity, given the high level of consumption of SSD and the lack of nutritional value of these products, action needs to be taken to reduce consumption, particularly in children. There is a compelling case for the introduction of public policy to reduce SSD consumption in the population. The introduction of a tax on SSDs in combination with other public health interventions has the potential to have a measurable effect on the scale of the epidemic of childhood obesity.